Survei Tingkat Ketrampilan Dasar Permainan Futsal Pada Ekstrakurikuler Futsal SMAN 1 Surade - Pandi Raksawiguna; Aria Kusuma Yuda; Rhama Nurwansyah (Universitas Singaperbangsa, 2021)
The purpose of this study was to determine the results of the basic skills level of the futsal game of SMAN 1 Surade students who took extracurricular activities in Sukabumi Regency, whether they were in the good or poor category. The subjects in this study were all members of the men's and women's futsal extracurricular activities with a total of 19 people. The data collection technique used in this research is descriptive quantitative research. The method used was a survey, while the data collection technique used tests, the tests in this study were in the form of instruments. The results of this study show that the level of futsal skills that follow extracurricular activities at SMAN 1 Surade, Sukabumi Regency which states in the